2015
DOI: 10.17770/etr2015vol2.268
|View full text |Cite
|
Sign up to set email alerts
|

The impact of human capital development on the economic and social development of a country: empirical study

Abstract: <p>Methodologically this research is based on the approach of many social scientists who argue that there is a bidirectional link: one runs from human capital development to economic growth and overall human development, when human capital helps increase national income and society development; the other runs from economic growth to human capital development, as the resources from national income are allocated to activities contributing to human capital development. The study aims to empirically verify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Human capital development on economic and social development has been revealed (Lonska & Mietule, 2015). The scholars argue that there is a bidirectional link: one runs from human capital development to economic growth and overall human development, when human capital helps increase national income and social development; the other runs from economic growth to human capital development, as the resources from national income, are allocated to activities contributing to human capital development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Human capital development on economic and social development has been revealed (Lonska & Mietule, 2015). The scholars argue that there is a bidirectional link: one runs from human capital development to economic growth and overall human development, when human capital helps increase national income and social development; the other runs from economic growth to human capital development, as the resources from national income, are allocated to activities contributing to human capital development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This process will help to enhance institutional capacity and good governance. Thus, it is indicated that the human capital, which is a set of person's abilities and skills having a direct effect on one's economic and social activity potential, needs to be used to find the corrective measures (Lonska and Mietule, 2015). More importantly, FG6 explained that the Ethiopian government should strengthen the IGR system in the country.…”
Section: Concrete Comments On the Way Forward In Infrastructure Development In Ethiopiamentioning
confidence: 99%
“…In today's world, one of the key indicators of a country's sustainable socio-economic development is human capital (Lonska and Mietule, 2015;Kuznetsov, 2012;Liu, 2015;Visvizi and Daniela, 2019). The quality of human capital is increasingly influenced by physical culture and sports (Abelkalns at al., 2014;Letiagina, Grinevich, Gutko, 2019), which are effective resources for economic development in different countries (Beutler, 2008).…”
Section: Introductionmentioning
confidence: 99%